Multi-criteria method for the realistic placement of water quality sensors on pipes of water distribution systems. (June 2022) - Giudicianni, C.; Herrera, M.; Di Nardo, A.; Creaco, E.; Greco, R.
Abstract: This paper aims to solve three issues frequently present in the optimal placement of water quality sensors for protecting water distribution systems (WDSs) from both accidental and intentional contamination, namely i) computational intractability of the optimization problem as the size of the WDS increases, ii) unrealistic assumption that sensors are positioned at nodes, rather than on system pipes, and iii) neglecting site-specific practical conditions impacting on sensor installation. The three drawbacks were tackled by i) restraining the optimization to the hydraulic/topological-wise most important pipes, ii) introducing dummy nodes in the middle of these pipes as potential sensor locations, iii) applying a multi-criteria decision-making tool incorporating urbanistic and economic factors for selecting the most effective sensor locations. The method is tested on the WDS of the town of Parete (Italy), showing the manyfold benefits of the solution obtained. Highlights: Water quality sensors are located on pipes of water distribution system, as is in reality. Weighted topology is used for reducing the computational burden of optimization phase. Potential sensor locations are defined on the hydraulic/topological-wise most central pipes. Detection performance, economic and logistic criteria are used to select the best solution. A weighted multi-parametric Decision Support System for selecting the monitoring layout is proposed.